Genetic Analyses Suggest Separate Introductions of the Pine Pathogen Lecanosticta acicola Into Europe - Janoušek, Josef; Wingfield, Michael J; Monsivais, José G Marmolejo; Jankovský, Libor; Stauffer, Christian; Konečný, Adam; Barnes, Irene (Phytopathology, 2016)
Lecanosticta acicola is a heterothallic ascomycete that causes brown spot needle blight on native and nonnative Pinus spp. in many regions of the world. In this study we investigated the origin of European L. acicola populations and estimated the level of random mating of the pathogen in affected areas. Part of the elongation factor 1-α gene was sequenced, 11 microsatellite regions were screened, and the mating type idiomorphs were determined for 201 isolates of L. acicola collected from three continents and 17 host species. The isolates from Mexico and Guatemala were unique, highly diverse and could represent cryptic species of Lecanosticta. The isolates from East Asia formed a uniform and discrete group. Two distinct populations were identified in both North America and Europe. Approximate Bayesian computation analyses strongly suggest independent introductions of two populations from North America into Europe. Microsatellite data and mating type distributions indicated random recombination in the populations of North America and Europe. Its intercontinental introduction can most likely be explained as a consequence of the movement of infected plant material. In contrast, the spread of L. acicola within Europe appears to be primarily due to conidial dispersion and probably also ascospore dissemination.
Keywords: listy rostlin; populační genetika; zeměpis; genetická variace; Genetics, Population; Bayes Theorem; fylogeneze; mikrosatelitní repetice; Pinus; Genes, Mating Type, Fungal; Phylogeny; Europe; Geography; borovice; nemoci rostlin; Evropa; Microsatellite Repeats; Guatemala; Mexico; Plant Leaves; North America; Bayesova věta; Ascomycota; Plant Diseases; Genetic Variation; fungální geny pro párovací typ; Mexiko; Severní Amerika